Global DNA methylation and transcriptional analyses of human ESC-derived cardiomyocytes. Issue 1 (29th January 2014) - Gu, Ying; Liu, Guang-Hui; Plongthongkum, Nongluk; Benner, Christopher; Yi, Fei; Qu, Jing; Suzuki, Keiichiro; Yang, Jiping; Zhang, Weiqi; Li, Mo; Montserrat, Nuria; Crespo, Isaac; et al.
Abstract: With defined culture protocol, human embryonic stem cells (hESCs) are able to generate cardiomyocytes in vitro, therefore providing a great model for human heart development, and holding great potential for cardiac disease therapies. In this study, we successfully generated a highly pure population of human cardiomyocytes (hCMs) (>95% cTnT + ) from hESC line, which enabled us to identify and characterize an hCM-specific signature, at both the gene expression and DNA methylation levels. Gene functional association network and gene-disease network analyses of these hCM-enriched genes provide new insights into the mechanisms of hCM transcriptional regulation, and stand as an informative and rich resource for investigating cardiac gene functions and disease mechanisms. Moreover, we show that cardiac-structural genes and cardiac-transcription factors have distinct epigenetic mechanisms to regulate their gene expression, providing a better understanding of how the epigenetic machinery coordinates to regulate gene expression in different cell types.